The Effectiveness of Remotely Piloted Aircraft in a Permissive Hunter-Killer Scenario - Menthe, Lance (RAND Corporation, 2014)
The Air Force has begun to evaluate new concepts of operation for remotely piloted aircraft to meet future needs. This report analyzes the operational effectiveness of several such concepts in a specific, permissive "hunter-killer" mission, which illuminates trade-offs between platform size and number; sensor performance; and the complicating effects of darkness, fog, and cloud cover.